The impact of EPHA2 polymorphism on KSHV infectivity and KS prevalence among HIV/AIDS patients in South Africa - Blumenthal, Melissa Jayne Walcott (Division of Medical Biochemistry and Structural Biology, 2017)
Kaposi's Sarcoma (KS) is the most common Acquired Immune Deficiency Syndrome (AIDS)-related malignancy globally and is of particular significance in sub-Saharan Africa where, due to the Human Immunodeficiency Virus (HIV) epidemic, KS is the cause of significant morbidity and mortality. The oncogenic Kaposi's Sarcoma-associated herpes virus (KSHV) is the etiological agent of KS. Although KSHV seroprevalence in sub-Saharan Africa is high, not all AIDS patients develop KS, suggesting that host genetic factors contribute to susceptibility. The infection mechanism of KSHV in endothelial cells has recently been elucidated and highlights Eph Receptor A2 (EPHA2) as a specific host receptor for virus entry. Furthermore, EPHA2 has been implicated in oncogenesis and is upregulated in a number of cancers including KS. We therefore hypothesised that mutations in the KSHV host receptor's coding region could result in an altered EPHA2 that could affect susceptibility to KSHV infection and/or KS development among HIV/AIDS patients. To test our hypothesis, we studied three groups of HIV positive South African patients, namely patients with KS and patients without KS who were KSHV positive or KSHV negative. KS status was determined clinically and KSHV seroconversion was assessed using a combination of ELISAs to KSHV lytic antigen K8.1 and latency-associated nuclear antigen in patient plasma samples. All patients with KS were found to be KSHV seropositive as expected, while 45.45% of HIV positive patients without KS were found to be KSHV seropositive. From patient blood cells, we extracted genomic DNA and subsequently PCR amplified and sequenced the coding region of EPHA2, before comparing these sequences to the NCBI reference by multiple alignment. A number of variants were identified throughout the EPHA2 coding region and assessed statistically for association with KSHV susceptibility and/or KS prevalence. A novel heterozygous transition (c.2727C>T), which is predicted to result in the substitution of Cysteine for Arginine at amino acid position 858 in the functionally important tyrosine kinase domain, was identified as statistically associated with KSHV susceptibility as well as KS prevalence. Three additional missense variants (c.2254T>C, c.2257A>C and c.2688G>C) occurring in the tyrosine kinase domain and one occurring in the sterile-α-motif (c.2990G>T), a putative protein interaction domain, were found to be statistically associated with KS prevalence. This is the first study to investigate polymorphism in EPHA2 in HIV/AIDS patients in relation to susceptibility to KSHV infection and/or KS prevalence. The identification of variants in the KSHV entry receptor, EPHA2, opens new doors for the development of biomarkers involved in prognosis and treatment of KSHV-associated pathologies.